The role of factors in the development of hypoxia in children with secondary deforming osteoarthritis of the temporomandibular joint (Eurasian Journal of Research, Development and Innovation, 2025)
Secondary deforming osteoarthritis of the temporomandibular joint (SDO TMJ)in children is a multifactorial and polyetiological disease, which is complicated by respiratory apnea with its consequences in the form of hypoxia and acidosis. The main causes and factors of endogenous hypoxia in children with SDO TMJ in connection with general pathology and diseases of the ENT organs have not been sufficiently studied